(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Historical observations and various studies reveal that desertification is the result of both climatic and anthropic factors but recently the focus has been shifted towards the relationship of livestock and desertification. For centuries people believe that a major cause of desertification is the increasing number of livestock. Overgrazing done by the animals invites the natural or anthropogenic phenomena to occur freely. The more the number of animals, the great pressure it imposes on land. Recent studies show a wider picture. Rejuvenation of land is possible by pastoralism or by the adequate grazing behavior of animals. The focus of this paper will be towards the comparative study of livestock in the state of Rajasthan in the last two censuses that are 2007 and 2012. The opportunities which lay hidden due to the ignorance of people and study of recent desertification report given by ISRO suggest that there is a close relationship between livestock and desertification data. Allan Savory, who is a Zimbabwe Borne biologist, farmer, Game rancher and founder of Savory Institute has been leading entire desertification efforts in Africa and he uses an unorthodox approach for land rejuvenation. He believes in increasing the number of livestock on grassland or in any area rather than fencing them off for conservation.